NIVEL DE HIDRATACIÓN DE LOS JUGADORES DE FÚTBOL DE SALÓN, SEGÚN PROMEDIOS PONDERADOS DE UN CICLO DE ENTRENAMIENTOS EN LA CIUDAD DE ÑEMBY DURANTE LOS MESES DE SEPTIEMBRE Y OCTUBRE DEL AÑO 2023 (Fiep Bulletin - online, 2024)
The problem that was proposed to be evaluated especially considered the hydration needs of the players of an indoor soccer club during the competition in order to provide information on the quantification of fluid loss through the body weight monitoring technique and the formulation of the basic measures for optimal water replacement. Its general objective was to evaluate the hydration level of indoor soccer players, according to weighted averages of a training cycle of the “Fénix” Club in the city of Ñemby during the months of September and October of the year 2023. It was developed with a non-experimental design methodology, quantitative approach and descriptive level, on a population of 10 subjects through a census sample, using systematic records and a survey. Reflecting among its results that the composition of the indoor soccer team is included by the integration of the subjects with respect to the playing position, with differences in the average weights, whether on the left wing (n= 3) with 82, 20 Kg, the goalkeeper (n= 1) with 62.82 Kg, the pivots (n= 3) with 77.41, the posts or closures (n= 2) with 78.52 Kg and the right wing (n= 1 ) with 62.80 Kg. Concluding that the hydration level of indoor soccer players, according to weighted averages of a training cycle of the “Fénix” Club of the city of Ñemby during the months of September and October of the year 2023, It is a key point that should be adequately addressed to reduce the incidence of major risks, both physical and cognitive, given the high impact it has on athletes' performance.
Keywords: Hydration; Rehydration; Weight loss; Indoor soccer; Training